2022
DOI: 10.3390/medicina58040531
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotypes and Antiviral Resistance Mutations in Romanian HIV-HBV Co-Infected Patients

Abstract: Background and Objectives: Romania has one of the highest prevalence of hepatitis B virus (HBV) infection in human immunodeficiency virus (HIV) patients, mostly in those parenterally infected during childhood; nevertheless, there are scarce data on the virological profile of co-infection. The objective of this study was to assess the prevalence of HBV genotypes and antiviral resistance-associated mutations (RAMs) in these co-infected patients, in order to monitor the viral factors associated with the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Although both miR-122 and the levels of lymphocytes are related to the response to therapy, these connections are not fully understood, and they might be different from what has been discovered until now. This might be because of the differences in the viral genotypes encountered in Romanians as opposed to the other populations already studied [29,30] since HBV genotypes are important in the response to therapy [28]. Therefore, our study sets a trend towards future research projects which have the potential to better define the effects of HBV treatment on all individuals at a molecular level.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although both miR-122 and the levels of lymphocytes are related to the response to therapy, these connections are not fully understood, and they might be different from what has been discovered until now. This might be because of the differences in the viral genotypes encountered in Romanians as opposed to the other populations already studied [29,30] since HBV genotypes are important in the response to therapy [28]. Therefore, our study sets a trend towards future research projects which have the potential to better define the effects of HBV treatment on all individuals at a molecular level.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, recent studies have shown that the loss of HBsAg in chronic HBV patients receiving treatment is related to their viral genotype [28]. In Romania, the dominant viral genotypes are A and D [29], which are different from the dominant genotypes found in Asian subjects (who are mostly involved in HBV studies) [30]. Since microRNAs and lymphocytes are also involved in treatment response, the differences in viral genotypes might affect them as well.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies in the last few years documenting the extensive burden of disease from common viral pathogens [230][231][232][233]. Given that for many of the most common viral pathogens, there is a pattern of increasing resistance to antiviral drugs and recombinant strains emergence [234][235][236][237][238][239], and many viruses are associated with severe persistent pathological features [240][241][242][243][244][245], the research on natural antiviral substances is ever more important.…”
Section: Capsaicin As An Antiviral Agentmentioning
confidence: 99%